2014
DOI: 10.1089/ast.2014.1171
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Planetary Rotation Period for Ocean Heat Transport

Abstract: The climate and, hence, potential habitability of a planet crucially depends on how its atmospheric and ocean circulation transports heat from warmer to cooler regions. However, previous studies of planetary climate have concentrated on modeling the dynamics of atmospheres, while dramatically simplifying the treatment of oceans, which neglects or misrepresents the effect of the ocean in the total heat transport. Even the majority of studies with a dynamic ocean have used a simple so-called aquaplanet that has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…But subsequent investigations with simplified climate models (Haberle et al 1996) and general circulation models (GCMs) (Joshi et al 1997;Joshi 2003;Merlis & Scheider 2010;Edson et al 2011;Showman et al 2010Showman et al , 2013Leconte et al 2013;Yang et al 2013Cullum et al 2014;Hu & Yang 2014;Carone et al 2014Carone et al , 2015Carone et al , 2016Wordsworth 2015;Way et al 2016;Kopparapu et al 2016Kopparapu et al , 2017Noda et al 2017;Fujii et al 2017) have demonstrated that energy transport from the day to night hemisphere is generally sufficient to avoid atmospheric collapse across a wide range of atmospheric compositions and rotation periods.…”
Section: Introductionmentioning
confidence: 99%
“…But subsequent investigations with simplified climate models (Haberle et al 1996) and general circulation models (GCMs) (Joshi et al 1997;Joshi 2003;Merlis & Scheider 2010;Edson et al 2011;Showman et al 2010Showman et al , 2013Leconte et al 2013;Yang et al 2013Cullum et al 2014;Hu & Yang 2014;Carone et al 2014Carone et al , 2015Carone et al , 2016Wordsworth 2015;Way et al 2016;Kopparapu et al 2016Kopparapu et al , 2017Noda et al 2017;Fujii et al 2017) have demonstrated that energy transport from the day to night hemisphere is generally sufficient to avoid atmospheric collapse across a wide range of atmospheric compositions and rotation periods.…”
Section: Introductionmentioning
confidence: 99%
“…As has been shown, accurately modeling the influence of oceans on global heat transfer is crucial for simulating warm planetary climates (e.g., Cullum et al, 2014). However, most 3-D models simulating warm climates do not dynamically couple the atmospheric and ocean circulations, and instead assume a static heat flux into the ocean (e.g., Bin et al, 2018;Shields et al, 2013;Wordsworth et al, 2015).…”
Section: The Importance Of Atmospheric-ocean Heat Transportmentioning
confidence: 99%
“…These are, in addition to the more obvious parameters such as atmospheric mass and composition, parameters that we do not know for potentially habitable rocky extrasolar planets. While it is important to understand how these parameters may influence the climate, such as studied for the rotation rate by Yang et al (2014Yang et al ( , 2013 and Del Genio & Suozzo (1987) or the oceanic heat transport (Yang et al 2013;Cullum et al 2014), accounting for all possible combinations of boundary parameters in addition to the unknown atmospheric composition and mass is rather impractical. Hence, 1D models are important to assess the main aspects of planetary climate, or in our case habitability, but also for atmospheric biomarker studies with coupled climate chemistry models.…”
Section: Introductionmentioning
confidence: 99%